2015
DOI: 10.7324/japs.2015.50817
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity following separate administration of two phosphodiesterase-5 inhibitors (sildenafil and tadalafil) and opioid (tramadol); evaluation of possible reversal following their withdrawal

Abstract: The use of phosphodiesterase-5 inhibitors (PDE5i) and tramadol in the absence of erectile and ejaculatory dysfunctions in Nigeria has become a norm. In this study, we comparatively assess the effects of chronic use of these drugs on hepatotoxicity. Fifty male albino wistar rats weighing 180-200g were randomly assigned into 5 groups (n=10) as follows; control, sildenafil (1mg/100g b.w), tadalafil (1mg/100g b.w), tramadol (2mg/100g b.w) and sildenafil+tramadol treated group (1mg/100g and 2mg/100g b.w, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
5
11
0
Order By: Relevance
“…In our previous study, combined administration of sildenafil and tramadol was shown to significantly alter liver functions but these alterations were reversed following withdrawal of treatment with the drugs (Nna et al, 2015b). Our findings also revealed that, combination of sildenafil and tramadol exhibited hypolipidemic effect with poor reversibility following withdrawal of treatment.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In our previous study, combined administration of sildenafil and tramadol was shown to significantly alter liver functions but these alterations were reversed following withdrawal of treatment with the drugs (Nna et al, 2015b). Our findings also revealed that, combination of sildenafil and tramadol exhibited hypolipidemic effect with poor reversibility following withdrawal of treatment.…”
Section: Introductionsupporting
confidence: 52%
“…Tramadol has been reported to decrease cortisol concentration (Oka et al, 2015), and increase basal metabolic rate and triiodothyronine concentration (Oka et al, 2015). Tramadol has also been reported to significantly alter liver functions (Nna et al, 2015b). In haematological studies conducted by Elyazji et al (2013), tramadol was found to increase WBC count, lymphocyte count and MCV, but decreased PCV, Hb, RBC count, MCH, MCHC and platelets count.…”
Section: Introductionmentioning
confidence: 94%
“…Sildenafil citrate (Maxheal Laboratories Pvt Ltd, India), tadalafil (Pfizer, India) and tramadol hydrochloride (Glow Pharma Pvt Ltd, India) were purchased from Unipervit Pharmacy, Ikot Omin, Calabar, Nigeria. The different drugs were orally administered, once, every two days as used in our previous reports (Nna, Akpan, Okon, & Atangwho, ; Nna, Akpan, & Osim, ), while the control group received normal saline as vehicle. The drugs were administered to both treatment and recovery groups for 8 weeks, after which animals in the treatment groups (A) were sacrificed under chloroform anaesthesia and the left testis and epididymis carefully harvested for semen analysis, oxidative stress assessment and histopathological examination.…”
Section: Methodsmentioning
confidence: 99%
“…The phosphodiesterase type 5 inhibitor, sildenafil citrate (SC) and the opioid, tramadol are substances that have been reported to be highly abused in Nigeria [1,2,3]. The reasons behind their abuse are prolongation of erection, postponement of ejaculation and enlargement of genital size [4].…”
Section: Introductionmentioning
confidence: 99%
“…The implication of this is constant bombardment of the liver due to high concentrations of these medications. Both SC and tramadol administered separately and in combination have been reported to damage the liver [2,7,8] by causing oxidative stress [7,9].…”
Section: Introductionmentioning
confidence: 99%